Traditional taekwondo : core techniques, history, and philosophy - Cook, Doug (YMAA Publication Center, 2006)
This book describes in detail, the history and evolution of Taekwondo from its ancient roots to modern day applications. Also included are exercises in Ki development or internal energy development, meditation practice and 'core' practical self-defense strategies. This work focuses on the traditional aspects of Taekwondo rather than on its sportive component.